Effects of dietary CLA supplementation, parity and different concentrate levels before calving on immunoglobulin G1, G2 and M concentrations in dairy cows. (October 2017) - Eger, Melanie; Horn, Jana; Hussen, Jamal; Schuberth, Hans-Joachim; Scharf, Maria; Meyer, Ulrich; Dänicke, Sven; Bostedt, Hartwig; Breves, Gerhard
Abstract: Peripartal dairy cows exhibit a higher susceptibility for infectious diseases, which might be linked to the negative energy balance occurring at the onset of lactation. A dietary supplementation of conjugated linoleic acids (CLA) may reduce milk fat yield and subsequently lower the energy deficit. The utilization of immunoglobulins (Ig) for colostrogenesis might impair humoral immunity in peripartal dairy cows; therefore this study investigated the effects of a CLA supplement, parity and different dietary energy levels on plasma and colostrum IgG1, IgG2 and IgM levels in dairy cows and their calves. Blood samples were collected from 64 cows from 21 days before until 56 days after parturition and colostrum samples for the first 3 days of lactation. Plasma immunoglobulin concentrations of 19 calves were determined before colostrum uptake. Neither plasma IgG1, nor IgG2 levels were affected by CLA or dietary energy level. However, immunoglobulin levels were affected by parity. Heifers possessed the lowest IgG1 concentrations. IgG2 concentrations were highest in cows with 2 lactations prior to parturition and in heifers after parturition. Plasma IgM levels were characterized by a sharp decrease 3 days prior to parturition and were scarcely affected by the feeding regimen or parity. Generally, immunoglobulin levels appear to be mostly independent from the peripartal energy balance of the cows and are not influenced by dietary CLA. However, pronounced differences among parities for IgG1 and IgG2 were revealed which should be further evaluated. Highlights: Immunoglobulin levels were not altered by feeding conjugated linoleic acids. Immunoglobulin levels were scarcely affected by peripartal energy balance. Parity had a major impact on plasma immunoglobulin G1 and G2 levels.